Adressaten for Leonora Christinas selvbiografi - Akhøj Nielsen, Marita; Schøsler, Lene (Danske Studier, 2024)
The editions of Leonora Christina’s French autobiography (2021) and Otto Sperling’s biography of Leonora Christina (2022) have provided prerequisites for a thorough study of the two works and of their mutual relationship, including the question of the autobiography’s addressee. At least since 1730, Otto Sperling has been designated as the addressee, which Sebastian Olden-Jørgensen has argued against in two articles from 2022. Instead, he has put forward the hypothesis that the autobiography is addressed to Admiral Henrik Bielke. This hypothesis has motivated the present study. The procedure has been to collate the two texts and bring out all agreements and deviations (section 2). Next, the autobiography has been read closely to collect all information about the addressee (section 3), and the other sources for the addressee question have been scrutinized (section 4). Finally, the importance of the addressee question for the perception of the autobiography is assessed: Is it indeed a private letter or a defense addressed to an international audience? (section 5). The main results of the investigation are that the autobiography is not conform to the characteristics of a private letter, and that Otto Sperling was probably the “Monsieur” to whom the autobiography is directly addressed, but that the true addressee was the European network of the Ulfeldt family and other influential circles.